Comment on Akil et al.: Nonintubated versus intubated lung volume reduction surgery in patients with end-stage lung emphysema and hypercapnia - Trudzinski, Franziska; Hoffmann, Hans; Langer, Frank; Kontogianni, Konstantina; Mahlmann, Jan; Eberhardt, Ralf (Journal of Clinical Medicine, 2025)
We read with interest the study by Akil et al [...]
Gesehen am 29.09.2025